Comprehensive molecular analysis of 61 Egyptian families with hereditary nonsyndromic hearing loss. Issue 1 (23rd April 2020) - Budde, Birgit S.; Aly, Maha Abdelgaber; Mohamed, Mostafa R.; Breß, Andreas; Altmüller, Janine; Motameny, Susanne; Kawalia, Amit; Thiele, Holger; Konrad, Kathryn; Becker, Christian; Toliat, Mohammad R.; Nürnberg, Gudrun; et al.
Abstract: Nonsyndromic hearing loss is an extremely heterogeneous disorder. Thus, clinical diagnostics is challenging, in particular due to differences in the etiology of hearing loss between populations. With this study, we wanted to elucidate the genetic basis of hearing loss in 61 consanguineous Egyptian families. In 25 families, linkage analysis was used as a prescreening to identify regions for targeted sequencing of candidate genes. Initially, the coding regions of 12 and later of 94 genes associated with hearing loss were enriched and subjected to massively parallel sequencing (MPS) with diagnostic yields of 36% and 75%, respectively. Causative variants were identified in 48 families (79%). They were found in 23 different genes with the majority being located in MYO15A (15.3%), SLC26A4 (9.7%), GJB2 (8.3%), and MYO7A (6.4%). As many as 32 variants were novel ones at the time of detection. Five variants were shared by two, three, or even four families. Our study provides a first survey of the mutational spectrum of deaf patients in Egypt revealing less GJB2 variants than in many European populations. It underlines the value of targeted enrichment of well‐selected deafness genes in combination with MPS in the diagnostics of this frequent and genetically heterogeneous disorder. Abstract :